Pregnancy course and perinatal outcomes in women with congenital heart valve disease - Yu. V. Bukhonkina1; R. I. Stryuk; G. V. Chizhova; V. B. Nemirovsky (Кардиоваскулярная терапия и профилактика, 2009)
Aim. To assess the pregnancy course and perinatal outcomes in women with congenital heart valve disease (CHVD).Material and methods. In total, 150 medical histories of pregnant women with corrected CHVD (CCHVD; n=61) and non-corrected CHVD (NCHVD; n=89) were retrospectively analysed. All women gave birth at the specialised maternity centre in Moscow and the perinatal centre in Khabarovsk.Results. The features of CHVD in pregnant women reflected the population patterns and were represented by interventricular and interatrial septal defects, aortal coarctation, open arterial duct, pulmonary artery stenosis, and corrected “blue” heart valve disease. Approximately 20% of the women learnt about their disease during the current pregnancy. In most women, the pregnancy course was uncomplicated, but in 9,8% (n=6) of CCHVD and 14,8% (n=13) of NCHVD women, heart failure (HF) symptoms developed and progressed at Weeks 28-32, when the hemodynamic load on cardiovascular system is maximal. Hospitalization and adequate treatment of these patients improved their clinical status and prolonged the pregnancy up to physiological terms. Over 50% of the women had cesarean delivery, despite no evidence of cardiovascular decompensation.Conclusion. The first delivery in most women with CCHVD and NCHVD took place at young age. Cardiovascular decompensation was registered at Weeks 28-32, when the hemodynamic load is maximal.